2013
DOI: 10.1111/echo.12481
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Prognostic Value of Stress Echocardiography in Obese, Morbidly Obese, and Super Obese Patients Referred for Bariatric Surgery

Abstract: Stress echocardiography is feasible in the morbidly obese patients. Patients with higher BMI were more likely to undergo dobutamine SE and have higher incidence of poor acoustic windows and contrast use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Two studies have evaluated the feasibility of transthoracic SE in obese patients awaiting bariatric surgery. Both studies showed excellent feasibility with contrast echocardiography 8 9. Our present findings extend the results of the previous two studies as our study was prospective and multicentre in design and, importantly, evaluated the performance of SE in a ‘real-world’ clinical service with obese patients referred for assessment of known or suspected CAD, not just specifically for preoperative risk stratification.…”
Section: Discussionsupporting
confidence: 78%
“…Two studies have evaluated the feasibility of transthoracic SE in obese patients awaiting bariatric surgery. Both studies showed excellent feasibility with contrast echocardiography 8 9. Our present findings extend the results of the previous two studies as our study was prospective and multicentre in design and, importantly, evaluated the performance of SE in a ‘real-world’ clinical service with obese patients referred for assessment of known or suspected CAD, not just specifically for preoperative risk stratification.…”
Section: Discussionsupporting
confidence: 78%
“…However, only dobutamine SE was evaluated. More recently, Supariwala and coworkers performed a single-center retrospective analysis in patients with BMI >30kg/m 2 referred for bariatric surgery and also found that just 1% of studies were nondiagnostic, specifically due to poor image quality ( 13 ).…”
Section: Comparison With Other Echocardiographic Studiesmentioning
confidence: 99%
“…This is the first study in patients with class III obesity to directly compare the feasibility and interpretability of DSE with and without the use of intravenous contrast enhancement, both cumulatively and on a segment-by-segment basis. [13][14][15][16][17][18][19] The results indicate that in patients with class III obesity, DSE performed using intravenous contrast enhancement is superior to DSE performed without intravenous enhancement, particularly with regard to visualization of the lateral and anterior segments. Moreover, DSE without intravenous contrast was associated with a significantly higher frequency of poor-or non-visualization of [?]…”
Section: Discussionmentioning
confidence: 89%
“…Nine prior studies have evaluated patients with various degrees of obesity with transthoracic exercise stress echocardiography (ESE) or DSE to determine the feasibility of these studies in this population (4 studies), to assess prognosis based on the presence or absence of myocardial ischemia and other CV outcomes (8 studies). [12][13][14][15][16][17][18] or both (3 studies). Lerakis et al studied 611 patients whose BMI was [?]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation